Phylogenomics of the Carrot Genus (Daucus, Apiaceae) - Arbizu Berrocal, Carlos Irvin (2014)
•Premise of the study: We explored the utility of multiple nuclear orthologs for the taxonomic resolution of wild and cultivated carrot, Daucus species. •Methods: We studied the phylogeny of 92 accessions of 13 species and two subspecies of Daucus and 15 accessions of related genera (107 accessions total) with DNA sequences of 94 nuclear orthologs. Reiterative analyses examined data of both alleles using ambiguity codes or a single allele with the highest coverage, trimmed vs. untrimmed homopolymers; pure exonic vs. pure intronic data; the use of all 94 markers vs. a reduced subset of markers; and analysis of a concatenated data set vs. a coalescent (species tree) approach. •Key results: Our maximum parsimony and maximum likelihood trees were highly resolved, with 100% bootstrap support for most of the external and many of the internal clades. They resolved multiple accessions of many different species as monophyletic with strong support, but failed to support other species. The single allele analysis gave slightly better topological resolution; trimming homopolymers failed to increase taxonomic resolution; the exonic data had a smaller proportion of parsimony‐informative characters. Similar results demonstrating the same dominant topology can be obtained with many fewer markers. A Bayesian concordance analysis provided an overall similar phylogeny, but the coalescent analysis provided drastic changes in topology to all the above. •Conclusions: Our research highlights some difficult species groups in Daucus and misidentifications in germplasm collections. It highlights a useful subset of markers and approaches for future studies of dominant topologies in Daucus.